2017
DOI: 10.21474/ijar01/3292
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Attitude Toward Psychiatry in Umm Al-Qura University: A Cross-Sectional Study.

Abstract: Background: Several studies worldwide reported negative attitude toward psychiatry from medical students and interns. Despite the increasing demand for psychiatry and mental health services, psychiatrists' numbers are still low, and the field of psychiatry is still attracting a lower number of medical students. Objective: This study aims to measure the attitude of medical students and interns toward psychiatry in Umm Al-Qura University medical college, Makkah, Saudi Arabia. Method: A Cross-sectional study. A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 23 publications
5
9
2
Order By: Relevance
“…We found significant improvement in students’ thinking to be a psychiatrist in future (p=0.0002) post-term. This was also found in other previous studies,16 17 23 24 27–29 with few exceptions 18 22. There was an almost 23% surge in students agreeing to think about being a psychiatrist in the future, which is an asset that needs to be shaped further to reap dividends in the long run.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found significant improvement in students’ thinking to be a psychiatrist in future (p=0.0002) post-term. This was also found in other previous studies,16 17 23 24 27–29 with few exceptions 18 22. There was an almost 23% surge in students agreeing to think about being a psychiatrist in the future, which is an asset that needs to be shaped further to reap dividends in the long run.…”
Section: Discussionsupporting
confidence: 83%
“…We may speculate various reasons for it like negative opinions about psychiatry and mental illness in general held by clinicians from other fields of medicine affecting students, or them not finding it as financially rewarding as other specialties, students finding it tough for them to be able to show the kind of patience, empathy and compassion that a psychiatrist may hold for his patient, inability of teachers to inculcate these attributes in students, negative views about psychiatry and mental illness held by family members and perception of low prestige of psychiatry or the students’ interest lying elsewhere. Similar reasons were also cited in other studies 18 22. We need to dive deep into these contradictions so as to understand the relationship between various factors like classroom teaching, clinical rotation, association of students with consultants and postgraduate students in psychiatry who teach their undergraduate counterparts, role of good role models and movies in psychiatry which we feel might be useful in transforming or aiding the positive attitude post-term into seriously considering psychiatry as a career choice.…”
Section: Discussionmentioning
confidence: 62%
“…Our findings were much better than a study done by Sarhan et al 23 in which attitude towards only psychiatric patients and illness, and psychiatry and psychiatrists were statistically significant.…”
Section: Discussioncontrasting
confidence: 90%
“…These findings were consistent with studies done in last few years. 22,23,24 On comparison of the ATP-30 scale's four groups, it was found that attitude of the interns in three groups towards psychiatry significantly (statistically) increased after the posting of 15 days except the attitude towards psychiatric hospitals and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that community pharmacist should be aware of the various brands, supplements, and vitamins available in the market, the working mechanism and the side effects [25] , [26] . Previous studies [27] , [28] have shown that community pharmacists dispensing vitamins and supplements should be aware of the drugs interactions with vitamins and the various supplement products, the side effects of the products [29] . A study conducted by Song et al [30] found that there was a significant correlation between the health condition being treated and the nature of vitamins and supplements being used.…”
Section: Discussionmentioning
confidence: 99%